Implementation of Double Track System for Narcotics Abuse Perpetrators in Polres Tanjab Timur Jurisdiction - Febriana Nur Widyaningsih; Agung Pribadi Bayu Sukma (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2024)
This is a research article conducted to analyze the implementation of the double track system against narcotics abuse perpetrators in the jurisdiction of the East Tanjab Police according to the statutory system in force in Indonesia and the reality in the field. This research is juridical-empirical research with a sociological juridical research approach. The results showed that the double track system in the jurisdiction of the East Tanjab Police was applied in the form of giving rehabilitation sanctions to narcotics suspects. The results also show that the application of two-track criminal sanctions has been effective, although there are still some obstacles both from structural, technical, and surrounding community factors.